2011
DOI: 10.1103/physrevd.84.084025
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon stars

Abstract: We consider a gravitating spherically symmetric configuration consisting of a scalar field nonminimally coupled to ordinary matter in the form of a perfect fluid. For this system we find static, regular, asymptotically flat solutions for both relativistic and nonrelativistic cases. It is shown that the presence of the nonminimal interaction leads to substantial changes both in the radial matter distribution of the star and in the star's total mass. A simple stability test indicates that, for the choice of para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
27

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(106 citation statements)
references
References 39 publications
(105 reference statements)
2
77
0
27
Order By: Relevance
“…The existence of slowly rotating fermion-boson stars was shown in [65], although no solutions were found in previous attempts [136]. Also see [73] for unstable solutions consisting of a real scalar field coupled to a perfect fluid with a polytropic equation of state.…”
Section: Varieties Of Boson Starsmentioning
confidence: 99%
“…The existence of slowly rotating fermion-boson stars was shown in [65], although no solutions were found in previous attempts [136]. Also see [73] for unstable solutions consisting of a real scalar field coupled to a perfect fluid with a polytropic equation of state.…”
Section: Varieties Of Boson Starsmentioning
confidence: 99%
“…In the cosmological context, the Lagrangian (1) was used in modeling the present accelerated expansion of the Universe [15,[32][33][34][35][36], in describing structure formation [37], and when considering compact configurations [36,38]. In doing so, a choice of the Lagrangian L m is, in general, not unique.…”
Section: Equations For Equilibrium Configurationsmentioning
confidence: 99%
“…However, it can be shown that, for instance, for static configurations, these Lagrangians, being substituted in the general Lagrangian (1), will give different equations for an equilibrium configuration [the Tolman-Oppenheimer-Volkoff (TOV) equations]. In the case of L m ¼ p, the TOV equation will have the same form as when f ¼ 1 [36,38]. On the other hand, the use of L m ¼ À" leads to the appearance of an extra term on the right-hand side of the TOV equation associated with the nonminimal coupling [see Eq.…”
Section: Equations For Equilibrium Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case f → 1 corresponds to the absence of a direct coupling between matter and the scalar field, when the two sources are coupled only via gravity. In the cosmological context, the interaction Lagrangian (1) was used in modeling the present accelerated expansion of the Universe [34,[49][50][51][52][53], in describing structure formation [54], and when considering compact configurations [53,55]. In doing so, a choice of the Lagrangian L m is, in general, not unique.…”
Section: Derivation Of the Equations For Equilibrium Configurationsmentioning
confidence: 99%